Balkán-kép vagy a Balkán képei? : a Balkán-félsziget a magyar katonai utazási irodalomban - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2012)
The Balkan Peninsula had played an important role in the history of Hungarian military travels from the 16th century. As a consequence of well known historical facts and processes the Ottoman Empire dominated the peninsula was the main target of the Hungarian military travels during centuries and at the same time determined the Hungarian vision of the peninsula. The interest of Hungarian military profession had not decreased in the later centuries towards this land. In the 19th century first the Hungarian Revolution of 1848–49, then the political and power shifts of the Balkans in the second half of the century and finally the First World War meant those historical nodes that enriched by leaps and bounds the Hungarian military literature dealing with the region, its people and landscape. Beyond the geographical neighbourhood the foreign policy interest of the Austro-Hungarian Empire towards the Balkans also encouraged that Hungarian soldiers fought in the wars of the Balkan Peninsula. They have left us important geographical and military resources. By these works it is well reconstructed how the Hungarian society thought about nations of the Balkans and also how the Hungarian vision and military thinking changed about the Peninsula. This study takes stock of the most important Hungarian military travellers demonstrating the wars they took part in and outlines the above mentioned changing vision of the Balkans. From a methodological point of view the author draws a parallel between the birth of the Balkan states and the important era of the Hungarian military travels. The essay examines the period from 1849 to 1918 and is a continuation of the writer‟s study about Hungarian military travellers in Albania.